Enhancing cell viability and GABA production in fermented milk using fruit juice-coated alginate microencapsulated Lactiplantibacillus plantarum B7 during storage - Pannerchelvan, Sangkaran; Jawlan, Louise Lorna Lanne; Wasoh, Helmi; Mohamed, Mohd Shamzi; Faizal Wong, Fadzlie Wong; Mohd Sobri, Mohamad Zulfazli; Mohamad, Rosfarizan; Halim, Murni (Springer Science and Business Media Deutschland, 2025)
Gamma-aminobutyric acid (GABA) is a non-protein amino acid with diverse health benefits, prompting interest in its incorporation into functional foods. In vitro probiotic characterization of Lactiplantibacillus plantarum B7, selected for its superior GABA production in a previous study, was performed before studying its microencapsulation using alginate coated with apple and pear juices to enhance cell viability and stability during storage in fermented milk. Both apple and pear juice-coated alginate microcapsules (AL-A + B7 and AL-P + B7) showed superior encapsulation, GIT condition tolerance, and release efficiency compared to alginate-only microcapsules. In comparison, free-cell L. plantarum B7 exhibited higher GABA production (2.59 ± 0.03 g/L), cell growth (8.96 ± 0.02 log CFU/mL), and the lowest pH (5.27 ± 0.06) at 48 h of fermentation. Among microencapsulated samples, AL-A + B7 showed the highest cell growth (8.93 ± 0.05 log CFU/g), GABA production (2.45 ± 0.05 g/L), and a lower pH (5.32 ± 0.06). During storage, AL-A + B7 retained higher viable cell counts (8.34 ± 0.13 log CFU/g) and improved GABA levels (3.90 ± 0.25 g/L) after 28 days, while free-cell samples showed a significant decline in cell count (from 8.96 ± 0.05 to 5.51 ± 0.13 log CFU/mL) and no significant improvement in GABA. These results highlight that apple juice-coated alginate (AL-A + B7) enhances the stability and viability of L. plantarum B7 during storage, while also promoting GABA production under storage conditions. These findings suggest its potential application in the development of functional foods with possible health benefits.